HAPPINESS IN RAJKUMAR HIRANI'S 3 IDIOTS MOVIE (2009):AN INDIVIDUAL PSYCHOLOGICAL APPROACH - HAPSARI, ARVIANA RATIH (2011)
This research paper reveals how the effort of major character tries to get happiness influences his personality reflected in 3 Idiots movie directed by Rajkumar Hirani published in 2009 which are analyzed through an individual psychological approach. The research based on its structural elements and to analyze by using individual psychological approach. This research is belong to qualitative research. The type and the data source which are used, namely primary and secondary data. The primary data source is the movie itself. The secondary data sources are taken from books and other sources which support the analysis. The method of the data collection is library research and the technique of the data analysis is descriptive analysis. Based on the analysis, the researcher draws two conclusions, first based on the structural analysis; Rajkumar Hirani wants to deliver moral message that a person must try and not give up reaching something that they want with any efforts, prayers and patiences. Education is not about success; it is about pursuing excellence and doing what someone passionate about. From the structural analysis, it shows that each of the structural elements are interrelated to each other. Second based on the individual psychological analysis, the writer draws that the movie represents Rajkumar Hirani's response about education. It can be seen that the spirit can influence the character of Rancho in achieving the happiness.